Public and elite opinion on international human rights law: Completing the causal chain of the domestic compliance mechanism. Issue 4 (8th August 2019) - Kim, Matthew
Abstract: Why do states comply with international human rights law? Scholars have looked to domestic politics to suggest a constituency-driven domestic compliance mechanism. However, it is unclear if strong public support for compliance leads to greater willingness to comply among elected officials. This study is the first to empirically demonstrate the complete causal chain of a constituency-driven domestic compliance mechanism. Using a survey experiment, this study first finds that a strong state commitment to UN Norms on the Responsibilities of Transnational Corporations (RTNC) increases public support for compliance. Using a parallel lab-in-the-field experiment of sitting legislators, the study then finds that a strong state commitment to RTNC is similarly associated with increased elite support for compliance. Finally, the study finds that public demand for compliance is associated with even greater elite support for compliance. Public demand for compliance seems to elicit elite willingness to comply by raising reputational concerns.